2013
DOI: 10.1111/epi.12356
|View full text |Cite
|
Sign up to set email alerts
|

Minimum requirements for the diagnosis of psychogenic nonepileptic seizures: A staged approach

Abstract: SUMMARYAn international consensus group of clinician-researchers in epilepsy, neurology, neuropsychology, and neuropsychiatry collaborated with the aim of developing clear guidance on standards for the diagnosis of psychogenic nonepileptic seizures (PNES). Because the gold standard of video electroencephalography (vEEG) is not available worldwide, or for every patient, the group delineated a staged approach to PNES diagnosis. Using a consensus review of the literature, this group evaluated key diagnostic appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
227
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 646 publications
(257 citation statements)
references
References 151 publications
5
227
0
6
Order By: Relevance
“…We included adults with definite PNES according to recent consensus recommendations 13. They were recruited from the EEG/Epilepsy Unit of the Department of Clinical Neurosciences (including outpatients and inpatients).…”
Section: Methodsmentioning
confidence: 99%
“…We included adults with definite PNES according to recent consensus recommendations 13. They were recruited from the EEG/Epilepsy Unit of the Department of Clinical Neurosciences (including outpatients and inpatients).…”
Section: Methodsmentioning
confidence: 99%
“…1 There is a previous history of psychological trauma or psychiatric co-morbidities in approximately 70% of patients. 1 Up to half of patients have a precipitating life event.…”
Section: Case Reportmentioning
confidence: 99%
“…1 There is a previous history of psychological trauma or psychiatric co-morbidities in approximately 70% of patients. 1 Up to half of patients have a precipitating life event. 1 The semiology of psychogenic non-epileptic seizures can resemble most types of epileptic seizures but some aspects may increase the clinical suspicion: triggering by psychological stress, long duration, fluctuating course, asynchronous movements, pelvic thrusting, forced eye closure, ictal crying, memory recall and signs of emotional distress.…”
Section: Case Reportmentioning
confidence: 99%
“…These have been predicated in large part by a realisation that you can only reliably diagnose a functional disorder by demonstrating typical positive features on assessment [12,13]. It cannot be diagnosed on the basis of associated psychosocial factors and neither is it a diagnosis of exclusion.…”
Section: Advances In Diagnosis and Classification Of Functional Neuromentioning
confidence: 99%
“…An important study of witnesses of vEEG-confirmed cases highlighted how commonly they report features 'sometimes', 'often' or 'always' that might be thought to be typical of ES such as ''frothing at the mouth'' (19 %), ''head turning'' (35 %), ''lip smacking or chewing'' (49 %) and ''eyes open'' (66 %)-clinicians beware [38]! An international consensus group collaboration report from the International League Against Epilepsy aimed to 'develop clear guidance on standards for the diagnosis of PNES' [13]. They distinguished four diagnostic levels: possible, non-clinician witnessed event or self-reported, and no epileptiform activity in routine or sleep-deprived interictal EEG; probable, clinician witnessed event with signs typical of NES (as outlined above), with no epileptiform activity found in routine or sleep-deprived interictal EEG; clinically established clinician witnessed event with signs typical of NES, with no epileptiform EEG activity; and documented event with no epileptiform activity immediately before, during or after ictus captured on ictal vEEG, with typical NES semiology.…”
Section: Dissociative (Non-epileptic) Seizuresmentioning
confidence: 99%